2021
DOI: 10.25259/sni_621_2021
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem intraparenchymal schwannoma: A case report and literature review

Abstract: Background: Intracranial intraparenchymal schwannomas (IS) are rare tumors that have mainly been described in case reports. Here, we report on a case of a brainstem IS and included a comprehensive literature review. Case Description: A 74-year-old man presented with progressive gait disturbances. CT- and MRI-imaging revealed a contrast-enhancing mass accompanied by a cyst in the dorsolateral pons. Hemangioblastoma was suspected and surgery was advised. During surgery, gross total resection of a non-invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…MINST is extremely rare, only one case was reported in the age group above 60 years [8]. The malignancy rate was approximately 5% in the age group above 60 years, which was slightly lower compared to other age groups [4].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…MINST is extremely rare, only one case was reported in the age group above 60 years [8]. The malignancy rate was approximately 5% in the age group above 60 years, which was slightly lower compared to other age groups [4].…”
Section: Discussionmentioning
confidence: 84%
“…Of these, 12.0% (18) of patients were over 60 years of age, which is unexpected. The incidence was higher in men in the age group under 30 years (male:female; 1.84:1); whereas, the pattern was reversed in the group above 60 years of age (male: female; 0.46:1) (Table 1) [4][5][6][7][8]. IS may originate anywhere in the intracranial region; however, appears to be more frequent in the supratentorial region during young age, whereas it is commonly located in the infratentorial region in individuals > 60 years of age [4].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…11 Reviewing the literature showed that the frontal and temporal lobes are the most common sites for developing IS. 8 There are no specific radiological features for the IS, and imaging findings are thought to be similar to the ISs. These features include calcification, cystic components, and edema.…”
Section: Discussionmentioning
confidence: 99%